PENERAPAN METODE PEMBELAJARAN PETA PIKIRAN UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA KULIAH FISIKA ZAT PADAT - Mutiara Siagian (Institut Pendidikan Tapanuli Selatan, 2018)
The purpose of this research was to determine the improvement of learning outcomes in fisika zat padat subject. The research method was quasi experimental with one group pre-test-post-test design. The population was all of students in physics study program semester VII STKIP Tapanuli Selatan totalling 25 students and and all of population became sample in this research. The technique of sampling was total sampling. Based on the data tabulation obtained the actual average gain for implementing of Mind Mapping method in improving learning outcomes was 39.05 where the normalized gain for implementation of Mind Mapping method to learning outcomes was 0,391, it was included in medium category. Based on the obtained results can be concluded that Implementation of Mind Maping method in fisika zat padat subject was included in medium category to improve learning outcomes.